Two-wavelength fundus autofluorescence and macular pigment optical density imaging in diabetic macular oedema - Waldstein, S M (Nature Publishing Group, 2012)
PURPOSE: To evaluate the application of 488 and 514 nm fundus autofluorescence (FAF) and macular pigment optical density (MPOD) imaging in diabetic macular oedema (DMO) and to demonstrate the typical imaging features. PATIENTS AND METHODS: A hundred and twenty-five eyes of 71 consecutive patients with diabetic retinopathy who underwent examination at a specialist university clinic employing a modified Heidelberg Retina Angiograph, using two different light sources of 488 and 514 nm wavelength, were retrospectively reviewed. MPOD images were calculated using modified Heidelberg Eye Explorer software. All images were evaluated by two independent masked graders. Features from FAF and MPOD images were correlated with optical coherence tomography (OCT) imaging findings and inter-grader variability, sensitivity and specificity were calculated using OCT as reference. RESULTS: Sixty-seven eyes had DMO on OCT. The inter-grader variability was 0.84 for 488 nm FAF, 0.63 for 514 nm FAF and 0.79 for MPOD imaging. Sensitivity and specificity for detection of DMO were 80.6 and 89.7% for 488 nm FAF; 55.2 and 94.8% for 514 nm FAF; and 80.6 and 91.4% for MPOD imaging. In 488 nm FAF and MPOD imaging, DMO was better visualised in comparison with 514 nm FAF imaging, P<0.01. MPOD revealed displacement of macular pigment by intraretinal cysts. CONCLUSION: MPOD imaging, and particularly its combination with 488 nm and 514 nm FAF, provides a valuable addition to OCT in the evaluation of DMO and is clinically useful in rapid en-face assessment of the central macula.